Numerical Simulation of Temperature Field in Rotary Kiln during Limonite Magnetization Roasting - Minghua Wang; Shuang Li; Xiaohong Lv; Shuoda Zhang; Zhenyu Gong; Taiping Lou (Kuangchan zonghe liyong, 2023)
Rotary kiln is an important industrial large-scale heating equipment. Measuring and calculating its internal heat and temperature distribution is of great significance for the reasonable design of rotary kiln and the setting of process parameters such as material flow rate and heating temperature in the process of operation, so as to achieve the purpose of saving energy. This paper analyzes the variation of heat, gas temperature, material temperature and kiln wall temperature with kiln length in the process of limonite reduction roasting in rotary kiln. The calculated results are in good agreement with the measured results. It is of certain significance to understand the distribution law of heat and temperature and reasonably arrange the process parameters of flue gas combustion and material distribution.